Transcriptome Analysis Reveals That Naphthenic Acids Perturb Gene Networks Related to Metabolic Processes, Membrane Integrity, and Gut Function in Silurana (Xenopus) tropicalis Embryos - Gutierrez-Villagomez, Juan Manuel; Martyniuk, Christopher J.; Xing, Lei; Langlois, Valerie S.; Pauli, Bruce D.; Blais, Jules M.; Trudeau, Vance L. (Frontiers in Marine Science, 2019)
Naphthenic acids (NAs) are oil-derived mixtures of carboxylic acids and are considered emerging contaminants with the potential to disrupt development of aquatic species. In the Oil Sands Region of Canada, NAs are components of the water released following processing of the bitumen-containing sand. The aim of this research was to identify potential mechanisms of toxicity of NA mixtures. Silurana (Xenopus) tropicalis embryos were raised in water spiked with commercial oil-derived NA extracts (S1 and S2) at a sub-lethal concentration (2 mg/L). The transcriptomic responses of the whole 4-day old embryos following exposure were assessed using a custom oligonucleotide microarray. Both NA mixtures induced embryonic abnormalities that included edema, and cardiac and gut abnormalities. Exposure to NAs also affected morphometric parameters and decreased total length, tail length, and interorbital distance of the embryos. Gene ontology analysis revealed that 18 biological processes, 5 cellular components, and 19 molecular functions were significantly enriched after both S1 and S2 exposures. Sub-network enrichment analysis revealed pathways that were related to phenotypic abnormalities; these included gut function, edema, and cartilage differentiation. Other notable networks affected by NAs included metabolism and cell membrane integrity. In a separate dose-response experiment, the expression of key genes identified by microarray (cyp4b1, abcg2, slc26a6, eprs, and slc5a1) was determined by Real-Time qPCR in S. tropicalis embryos exposed to the commercial NAs and to acid-extractable organics (AEOs) prepared from Oil Sands Process-Affected Water. In general, the RT-qPCR data agreed with the microarray data. In S. tropicalis embryos exposed to the AEOs, the mRNA levels of eprs (bifunctional glutamate/proline-tRNA ligase) and slcs5a1 (sodium/glucose cotransporter 1) were significantly decreased compared to the controls. Such changes are likely indicative of increased edema and disrupted gut function, respectively. These data suggest that NAs have multiple modes of action to induce developmental toxicity in amphibians. Some modes of action may be shared between commercial NAs and AEOs.